Counseling Generation Z with Social Media to Achieve Creativity - Amali, Muhammad Syafrie; Sherlly, Putri; Trahmawati, Tasya Aulia (Doctoral Program of Social Science, Pasundan University, 2025)
This community service program aims to enhance creativity and awareness of wise and productive social media use among Generation Z students at SMK Islam Said Na'um. The main issue addressed is the predominantly consumptive use of social media, which has not been optimally utilized as a tool for creativity development and entrepreneurship. The program employed a participatory counseling approach based on experiential learning, combining interactive lectures, hands-on workshops, and group discussions. A total of 27 students were selected using purposive sampling, considering their active engagement with social media platforms. The results indicate that interactive learning methods increased student participation, digital literacy awareness, and understanding of social media utilization for creative purposes and digital marketing. However, limitations in resources and the absence of a structured evaluation system constrained the assessment of long-term program impact. Overall, this program demonstrates positive outcomes in fostering creativity, entrepreneurial mindset, and productive social media usage among vocational high school students.